Coping Skills of Guidance and Counseling Students in Dealing with Academic Challenges at University - Siti Nurhalima; Abdul Saman; Sahril Buchori; Muhammad Amirullah (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2026)
Coping skills are essential abilities that help students manage various academic challenges throughout their university studies. Considering the increasing academic demands, assignment pressures, and diverse problems encountered by students in higher education, understanding the level of students' coping skills has become an important area of investigation. This study aims to describe the coping skills of Guidance and Counseling students in dealing with academic challenges. The study employed a descriptive quantitative approach involving 239 active students from the Guidance and Counseling Study Program at Makassar State University. The instrument used was a coping skills scale that has been translated and adapted into the Indonesian language. The data were analyzed using descriptive statistical techniques. The instrument demonstrated acceptable construct validity through item-total correlation analysis (r ≥ 0.30) and showed high reliability with a Cronbach's Alpha coefficient of 0.85, indicating that the instrument was appropriate for use in this study. The findings revealed that most students were categorized as having high and moderate levels of coping skills, indicating their ability to manage academic pressure and challenges adaptively. These findings emphasize the importance of academic and psychological support in higher education to assist students in strengthening their coping abilities when facing academic demands. Furthermore, the results provide a basis for developing campus-based interventions focused on enhancing coping skills, managing academic stress, and improving student resilience.